A reconstruction of extratropical Indo-Pacific sea-level pressure patterns during the Medieval Climate Anomaly - Goodwin, I.; Browning, S.; Lorrey, A.; Mayewski, P.; Phipps, S.; Bertler, N.; Edwards, Peter; Cohen, T.; Van Ommen, T.; Curran, M.; Barr, C.; Stager, J. (Springer, 2014)
Subtropical and extratropical proxy records of wind field, sea level pressure (SLP), temperature and hydrological anomalies from South Africa, Australia/New Zealand, Patagonian South America and Antarctica were used to reconstruct the Indo-Pacific extratropical southern hemisphere sea-level pressure anomaly (SLPa) fields for the Medieval Climate Anomaly (MCA ~700–1350 CE) and transition to the Little Ice Age (LIA 1350–1450 CE). The multivariate array of proxy data were simultaneously evaluated against global climate model output in order to identify climate state analogues that are most consistent with the majority of proxy data. The mean SLP and SLP anomaly patterns derived from these analogues illustrate the evolution of low frequency changes in the extratropics. The Indo-Pacific extratropical mean climate state was dominated by a strong tropical interaction with Antarctica emanating from: (1) the eastern Indian and south-west Pacific regions prior to 1100 CE, then, (2) the eastern Pacific evolving to the central Pacific La Niña-like pattern interacting with a +ve SAM to 1300 CE. A relatively abrupt shift to –ve SAM and the central Pacific El Niño-like pattern occurred at ~1300. A poleward (equatorward) shift in the subtropical ridge occurred during the MCA (MCA–LIA transition). The Hadley Cell expansion in the Australian and Southwest Pacific, region together with the poleward shift of the zonal westerlies is contemporaneous with previously reported Hadley Cell expansion in the North Pacific and Atlantic regions, and suggests that bipolar climate symmetry was a feature of the MCA.